2017
DOI: 10.1007/s00106-017-0422-0
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety

Abstract: The finding of a considerable prevalence of psychiatric comorbidities among ENT patients represents important information for the treating physician. BDI II and BAI were found to be reliable and easy to apply in the outpatient clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 180 publications
(248 reference statements)
0
2
0
Order By: Relevance
“…As for severe anxiety, the best predictors identified by logistic regression were age range 30 to 50 (P < 0.001, OR = 2.549), female sex (P < 0.001, OR = 2.349), negative life events (P < 0.001, OR = 3.454), and globus pharyngeus (P < 0.001, OR = 5.993). 37 who found the prevalence of moderate and severe depressive syndromes, anxiety disorders, and combined disorders to be 11.3% in otolaryngology outpatients. Also, the prevalence found by our study is much higher than the global prevalence of depression and anxiety reported by WHO 1 of 4.4% and 3.6%, respectively.…”
Section: As Shown Inmentioning
confidence: 99%
“…As for severe anxiety, the best predictors identified by logistic regression were age range 30 to 50 (P < 0.001, OR = 2.549), female sex (P < 0.001, OR = 2.349), negative life events (P < 0.001, OR = 3.454), and globus pharyngeus (P < 0.001, OR = 5.993). 37 who found the prevalence of moderate and severe depressive syndromes, anxiety disorders, and combined disorders to be 11.3% in otolaryngology outpatients. Also, the prevalence found by our study is much higher than the global prevalence of depression and anxiety reported by WHO 1 of 4.4% and 3.6%, respectively.…”
Section: As Shown Inmentioning
confidence: 99%
“…Next, we measured drug inhibition of the activity of HMG-CoA reductase using a wellestablished HMG-CoA reductase assay 30 . Both conjugates, G2-AT and G2-K-AT exhibited no inhibition of HMG-CoA reductase, while their hydrolyzed products displayed dramatic inhibition against HMG-CoA reductase ( Figure 1).…”
Section: Inhibition Of the Activity Of Hmg-coa Reductasementioning
confidence: 99%